(untitled) (Bangladesh Journal of Microbiology, 2021)
Bangladesh has achieved rapid industrialization in recent years. However, many of these industries lack proper effluent treatment plant and discharge untreated effluent laden with different heavy metals into the major rives that surround these industries, affecting the environment as well as human and animal health. Aiming to develop a sustainable effluent treatment plant, a heavy metal tolerant Bacillus pumillus isolated from polluted river water of Bangladesh was studied for its chromium bioremediation potential. Reduction of hexavalent chromium using the Sdiphenylcarbazide (DPC) method showed that whole cells of the Bacillus pumillus reduced 89.5%, 75%, 73% and 45% of 1.0, 2.5, 5 and 10mg/L Cr(VI) to Cr(III), respectively. This bacterium reduced 100% of 20mg/L Cr(VI) to Cr(III) within 8 hours, in a growth associated pattern. A 20kb plasmid was detected in this Bacillus pumillus, and loss of this plasmid did not cause complete impairment of chromium tolerance capacity, though the tolerance efficiency was reduced. The Bacillus pumillus studied in the current study therefore shows its potential to develop a sustainable chromium bioremediation method. Bangladesh J Microbiol, Volume 38, Number 1, June 2021, pp 27-30